2012
DOI: 10.1128/jvi.06720-11
|View full text |Cite
|
Sign up to set email alerts
|

Human Cytomegalovirus UL44 Concentrates at the Periphery of Replication Compartments, the Site of Viral DNA Synthesis

Abstract: The formation of replication compartments, the subnuclear structures in which the viral DNA genome is replicated, is a hallmark of herpesvirus infections. The localization of proteins and viral DNA within human cytomegalovirus replication compartments is not well characterized. Immunofluorescence analysis demonstrated the accumulation of the viral DNA polymerase subunit UL44 at the periphery of replication compartments and the presence of different populations of UL44 in infected cells. In contrast, the viral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
54
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(61 citation statements)
references
References 31 publications
7
54
0
Order By: Relevance
“…We note that it can be difficult to detect viral DNA synthesis in the initial electroporated cells (43). However, the distribution of UL44 in the UL84-null BAC electroporated cells (54) is likely to be due to a defect in viral DNA synthesis as we have previously demonstrated that UL44 is dispersed from viral replication compartments in the presence of an inhibitor of the viral DNA polymerase (46).…”
Section: Discussionmentioning
confidence: 87%
“…We note that it can be difficult to detect viral DNA synthesis in the initial electroporated cells (43). However, the distribution of UL44 in the UL84-null BAC electroporated cells (54) is likely to be due to a defect in viral DNA synthesis as we have previously demonstrated that UL44 is dispersed from viral replication compartments in the presence of an inhibitor of the viral DNA polymerase (46).…”
Section: Discussionmentioning
confidence: 87%
“…Within these compartments, viral DNA synthesis occurs concomitant with the accumulation of DNA replication proteins. In cells infected with the betaherpesvirus human cytomegalovirus (HCMV), these replication proteins include the accessory subunit of the viral DNA polymerase UL44 and the viral single-stranded DNA (ssDNA) binding protein UL57 (1)(2)(3). The HCMV replication compartment architecture has several distinguishing features (2,4).…”
mentioning
confidence: 99%
“…In particular, UL44 concentrates at the periphery of replication compartments. Viral DNA synthesis occurs within this peripheral layer, and newly replicated DNA is subsequently localized within the interior of replication compartments, which is where most UL57 is found (2). In contrast, studies of the alphaherpesvirus herpes simplex virus 1 (HSV-1) have revealed little evidence of comparable replication compartment organization (5,6).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently, "click chemistry" detecting EdU incorporation into replicating DNA was introduced to visualize active viral DNA synthesis in the periphery and interior of hCMV replication compartments (51). We combined EdU labeling with immunofluorescence to find that H3K4me2 colocalizes with nascent viral DNA within late replication compartments (Fig.…”
Section: Resultsmentioning
confidence: 99%